Creating a common trajectory: Shared decision making and distributed cognition in medical consultations - Katherine Lippa (The Beryl Institute, 2016)
The growing literature on shared decision making and patient centered care emphasizes the patient’s role in clinical care, but research on clinical reasoning almost exclusively addresses physician cognition. In this article, we suggest clinical cognition is distributed between physicians and patients and assess how distributed clinical cognition functions during interactions between medical professionals and patients with Multiple Sclerosis (MS). A combination of cognitive task analysis and discourse analysis reveals the distribution of clinical reasoning between 24 patients and 3 medical professionals engaged in MS management. Findings suggest that cognition was distributed between patients and physicians in all major tasks except for the interpretation of MRI results. Otherwise, patients and physicians collaborated through discourse to develop a common trajectory to guide clinical reasoning. The patients’ role in clinical cognition expands the concept of patient-centered care and suggests the need to optimize physician-patient distributed cognition rather than physician cognition in isolation.